Current practice and opinion regarding the use of therapeutic hypothermia after cardiac arrest survival in children: a survey of UK Paediatric Emergency Medicine consultants to inform the cold-PACK study. (26th December 2010) - Lyttle, M
Abstract : Background and aims: Therapeutic hypothermia improves neurological outcome in adults after cardiac arrest and term neonates with hypoxic ischaemic encephalopathy. There is currently no evidence to support its use in the paediatric population following cardiac arrest. This survey of UK Paediatric Emergency Medicine (PEM) consultants aims to ascertain current practice in UK, and attitudes and opinions to guide the feasability of a multicentre randomised controlled trial (RCT) of therapeutic hypothermia after cardiac arrest in children (the Cold-PACK study). Methods: In early 2010 UK PEM consultants were invited to complete a web based survey of current practice in therapeutic hypothermia and opinions regarding future research. Results: Following return of spontaneous circulation after cardiac arrest in children 58 % of respondents never cool, 35.5% seldom cool and 3.2 % often cool. The most common reasons for not cooling are 'not enough research evidence to support its use' (31.8%) and 'no equipment available to initiate cooling' (31.8%). 87.1% of responders did not know if therapeutic hypothermia improved outcome. Only 12.9% have a specific protocol for cooling, and there is wide variation in practice with respect to the depth of cooling. In those who cool, a range of cooling methods is employed, the most common of which is ice packs applied to skin (22.6%). 86% of respondents would support an RCT in the UK investigating the use of hypothermia after cardiac arrest, and 87% of respondents would be willing to commence therapeutic hypothermia in the Emergency Department. 80% felt that deferred consent could be used. Conclusions: There is wide variation in UK practice in the use of therapeutic hypothermia in PEM. This survey demonstrates clinical equipoise, and shows support for a future RCT of therapeutic hypothermia after cardiac arrest in children.